Persepsi Masyarakat Kota Padang Terhadap Peran Dewan Pengawas Syariah Dalam Mengawasi Pinjaman Online - Nadia Novita Sari; Rozalinda Rozalinda (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the perceptions of the people of Padang City regarding the role of the Sharia Supervisory Board (DPS) in supervising sharia-based online loans. The phenomenon behind this study is the low level of public understanding of the DPS's duties in supervising sharia-based online loans, which can reduce the effectiveness of supervision of these services. The objectives of this study are to explore the extent to which the public understands the role of the DPS in supervising online loans and to find out their views on sharia-based online loan services. The method used is in-depth interviews with two groups of respondents: the general public and individuals who have a deeper understanding of or are directly involved in sharia-based online loans. A total of ten respondents were interviewed, five of whom were members of the general public and five were individuals with more in-depth knowledge. The results of this study confirm that there is still a significant knowledge gap regarding the role of the Sharia Supervisory Board in supervising sharia-based online loans in Padang City. The general public only understands the basic principles of sharia without knowing the supervisory mechanisms carried out by the DPS, while the more informed group recognizes the importance of the DPS's role but still highlights the lack of transparency and consumer protection. The differences in views that emerged from the MUI, OJK, and service providers indicate that the implementation.